Evolution of supra-glacial lakes across the Greenland Ice Sheet - Sundal, Aud (2008)
We used 268 cloud-free Moderate-resolution Imaging Spectroradiometer (MODIS) images spanning the melt seasons 2003 and 2005-2007 to study the seasonal evolution of supra-glacial lakes in three different regions of the Greenland ice sheet. Lake area estimates were obtained by developing an automated classification method for their identification based on 250 m resolution MODIS surface reflectance data. Widespread supra-glacial lake formation and drainage are observed across the ice sheet, with a 2-3 weeks delay in the evolution of total supra-glacial lake area in the northern areas compared to the south-west. The onset of lake growth varies by up to one month inter-annually, and lakes form and drain at progressively higher altitudes during the melt season. The annual peak in total lake area is positively correlated with modelled annual runoff across all study areas, suggesting that local runoff governs seasonal variations in total supra-glacial lake area. Our results indicate that, in a future warmer climate (Meehl et al 2007), Greenland supra-glacial lakes can be expected to form at higher altitudes and over a longer time period than is presently the case, expanding the area and time period over which connections between the ice sheet surface and base may be established (Das et al 2008) and thereby potentially increasing ice sheet discharge (Zwally et al 2002).